Perceptions of Negative Workplace Gossip: A Self-Consistency Theory Framework. (May 2018) - Wu, Long-Zeng; Birtch, Thomas A.; Chiang, Flora F. T.; Zhang, Haina
We present and test a self-consistency theory framework for gossip: that perceived negative workplace gossip influences our self-perceptions and, in turn, this influences our behaviors. Using supervisor-subordinate dyadic time-lagged data (n = 403), we demonstrated that perceived negative workplace gossip adversely influenced target employees' organization-based self-esteem, which, in turn, influenced their citizenship behavior directed at the organization and at its members. Moreover, by integrating victimization theory into our framework, we further demonstrated that negative affectivity, an individual's dispositional tendency, not only moderated the self-consistency process but also predicted perceived negative workplace gossip. Our study therefore shifts attention to the target of negative workplace gossip and in doing so offers a promising new direction for future research. Implications to theory and practice are discussed.